The “soft life” phenomenon among young people: lifestyle or escape? - Mohd Shariff, Sazlin Suhalmie; Mohamad, Masilah (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
The “soft life” trend, popular on social media platforms like TikTok and Instagram, promotes a lifestyle focused on comfort, balance, and avoiding unnecessary stress. Many young people, especially Gen Z and millennials, see it as a response to traditional hustle culture, rising living costs, and uncertain job markets. The COVID-19 pandemic also influenced this shift by highlighting the importance of rest, health, and mental well-being. Supporters argue that the soft life encourages healthier work-life boundaries, self-care, and digital well-being while challenging toxic workplace expectations and allowing individuals to regain control over their time and energy.